Liabilities and contingencies of Brazilian football clubs - Oliveira, Monique Cristiane de; Borba, José Alonso (Contextus - Revista Contemporânea de Economia e Gestão, 2021)
This study aims to identify the characteristics of liabilities and contingencies of 20 clubs participating in the First and Second Division of the Brazilian Championship of 2017 that presented all financial statements from 2010 to 2018. It was found that 79 of 160 balance sheets analyzed presented uncovered liabilities and denoting effective problems of economic and financial unviability akthough no clubs broke effectively. The findings demonstrate that clubs cannot support themselves and eventually need to raise third-party resources. The study differs from previous research because it identifies the characteristics of liabilities, and provisions as present and future obligations for Brazilian football clubs. Thus, this research contributes by providing an overview of the indebtedness of Brazilian football clubs.